The interplay between persistent pathogen infections with tumor microenvironment and immunotherapy in cancer - Si Chen; Caihong Yao; Na Tian; Chunying Zhang; Yuemei Chen; Xuting Wang; Yue Jiang; Tonghao Zhang; Tingting Zeng; Yali Song (Cancer Medicine)
Abstract Background Chronic infections by pathogenic microorganisms play a significant role in cancer development, disrupting the body's immune system and microenvironment. This interference impairs the body's ability to eliminate these microorganisms promptly, allowing them to persist by evading immune defenses. Aims This study aimed to explore how chronic pathogenic infections influence the immune microenvironment, impacting tumorigenesis, cancer progression, and treatment strategies. Additionally, it seeks to investigate the effects of these infections on specific immune checkpoints and identify potential targets for immunotherapy. Methods We conducted searches, readings, and detailed analyses of key terms in databases like PubMed and Web of Science to evaluate the impact of chronic infections by pathogenic microorganisms on the immune microenvironment. Results Our analysis demonstrates a significant association between persistent chronic infections by pathogenic microorganisms and tumorigenesis. Notable impacts on the immune microenvironment include changes in immune cell function and the regulation of immune checkpoints, offering insights into potential targets for cancer immunotherapy. Discussion This study highlights the complex relationship between chronic infections and cancer development, presenting new opportunities for cancer immunotherapy by understanding their effects on the immune microenvironment. The influence of these infections on immune checkpoints emphasizes the crucial role of the immune system in cancer treatment. Conclusion Chronic infections by pathogenic microorganisms greatly affect the immune microenvironment, tumorigenesis, and cancer treatment. Unraveling the underlying mechanisms can unveil potential targets for immunotherapy, improving our comprehension of the immune response to cancer and potentially leading to more effective cancer treatments in the future.